TOXICIDADE DE NANOTUBOS DE CARBONO DE PAREDES MÚLTIPLAS EM MACRÓFAGOS - Müller, Betina (2015)
Carbon nanotubes (CNT) have unique properties that are of great interest to the biotechnology area. The idea of using CNTs as carriers of drugs, adjuvants for vaccines and biosensors, is attracting great interest from the scientific community. However, the biocompatibility and toxicity in vitro and in vivo of these structures need to be investigated. Thus, the aim of this study was to investigate the cytotoxicity caused by carbon nanotubes multi-walled (MWCNT) in peritoneal macrophages isolated from C57BL/6 mice and the secondary line RAW 264.7. To perform the in vitro test, cultured cells were treated with concentrations of 1 mg/mL and 5mg/mL MWCNT and 1μg/mL of lipopolysaccharide (LPS). The control group of cells with culture medium were cultured in DMEM medium supplemented with 10% fetal bovine serum (FBS) and the negative control at 100 mϻ hydrogen peroxide. The cells remained in treatments for periods of 24 and 48 hours. Then was determined cell viability through the exclusion method using trypan blue, which remained around 70%. After the biochemical cytotoxicity tests were conducted using the release of lactate dehydrogenase (LDH) in the cell supernatant, allowing to note that the concentrations of MWCNT were unable to cause any damage to the cell membrane, as well as any cytotoxic effect. These results confirm the microscopic images, which do not show cell death caused by MWCNT at these concentrations. The citotoxicity caused by MWCNT was evaluated by the measurement of nitric oxide (NO) and the gene expression of TNF-α and IL-1β. In these tests it was revealed that the toxicity was present in cells treated with the secondary line MWCNT, which did not have an increase in NO production and gene expression of cytokines analyzed.